CONTEMPORARY QUILOMBOS AND BIODIVERSITY PROTECTION: A THEORETICAL CONCEPTUAL APPROACH - Oliveira Vilela, Rodrigo; Lucio de Oliveira Campos, Neio (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
Quilombos were and still are structures that go beyond the typical feature of resistance. These communities are materializations of African social organization that was formed in Brazilian urban and rural areas. An important aspect of the presence of people of African origin in the Brazilian territory concerns the relationship between the quilombola communities and the environment that surrounds them.